Changing of Schools: How it affects the School Life Experiences of a Student - Ramandeep Singh; Mansi Chaudhary (International Journal of Engineering and Management Research, 2020)
The Pivot point of research carried out is to study the impact of changing of school in a student’s life and various effects it can have on school life experiences. Researcher has worked upon feedbacks gathered from individuals of different age and their experience accumulated from their own school lives. Analyst got reactions from 140 participants. The information was gathered using Google forms and it was investigated utilizing Google's analytical tools. It was found that changing of school had both merits and demerits given that how one perceives it and adapts according to the changes. People have different reasons for changing their schools. Factors like new region, culture and language of new place also acts as deciding factors for the adaptability and performance of newly admitted student.